Numerical algorithm based on the PDE method for solution of the Fokker Planck equation - Dolinska, M. (Вопросы атомной науки и техники, 2011)
This paper discus a fast and accurate algorithm for numerical solution of Fokker-Planck equation (FPE) based on the PDE (Partial Differential Equation) method. The PDE concepts and methods largely are used in computer simulation of fluid-dynamical systems. This method can be used for studying of stochastic beam dynamics in one dimensional phase space in the storage ring. The performances of the PDE-method are calculated using the stochastic cooling process in the CR storage ring (FAIR, Germany).